Physical characteristics, nutritive value and preference of zebu heifers for ensiled mixtures of corn cob, cassava peel and urea (2015)
In order to improve the feeding quality of corn cob and cassava peel for zebu cattle, a mixture of corn cob-cassava peel was ensiled with 0, 1, 2, and 3% of urea. Physical characteristics, chemical composition and in vitro digestibility of the silage mixtures were determined in a laboratory trial while the preference of cattle for the mixtures was evaluated using twelve Sokoto Gudali heifers in a cafeteria feeding trial. The experimental design adopted was the completely randomized design. Silage colour changed from white to yellow; smell from very pleasant to pungent; and texture from very firm to firm as the level of urea in the silage increased. The pH increased from 3.80 to 6.00 as level of urea in the mixture increased. Crude protein (CP) content of silage increased from 8.50 to 17.52% while acid detergent fibre (ADF) decreased from 34.13 to 30.90% as level of urea in the silage mixture increased. Organic matter digestibility (OMD) varied from 55.44 - 60.45%, and increased with addition of urea. Preference of zebu heifers for corn c'ob-cassava peel silage varied from 13.81 - 38.87%. Acceptability of silage reduced significantly as level of urea increased. Addition of urea to corn cob- cassava peel silage enhanced CP content and digestibility but physical attributes and acceptability of silage by cattle were adversely affected.